Development of an E-Module for the Computer Systems and Network Analysis Course - Niranti Jihan Sari; Jumadi M. Parenreng; Jamaluddin P. (Journal of Education for Creativity and Innovation, 2026)
Learning in the Computer Systems and Network Analysis course requires instructional materials that are well-structured, up-to-date, and easily accessible to support conceptual understanding and practical application within limited class time. This study aims to develop an e-module and to evaluate its validity, practicality, and effectiveness for use in the Computer Engineering Study Program at Universitas Negeri Makassar. The study employed a Research and Development (R&D) approach using the 4-D development model (define, design, develop, disseminate). The participants were students of the Computer Engineering Study Program, JTIK FT UNM. Data were collected through subject-matter expert validation, media expert validation, a student response questionnaire, and an instrument assessing learning outcomes after using the e-module. Data were analyzed using descriptive analysis. The results showed that the e-module achieved 100% in subject-matter expert validation and 100% in media expert validation, indicating that it was feasible/acceptable for use. In terms of effectiveness, student performance after using the e-module reached an average of 81.3% (very good category), while practicality analysis based on student responses yielded 70% (practical category). These findings indicate that the developed e-module meets feasibility criteria and supports the learning process. Therefore, the Computer Systems and Network Analysis e-module is deemed suitable as an instructional material to enhance learning quality in the Computer Engineering Study Program at Universitas Negeri Makassar.